Longitudinal assessment of lung function in extremely prematurely born children. Issue 3 (9th January 2018) - Lo, Jessica; Zivanovic, Sanja; Lunt, Alan; Alcazar‐Paris, Mireia; Andradi, Gwendolyn; Thomas, Mark; Marlow, Neil; Calvert, Sandy; Peacock, Janet; Greenough, Anne
Abstract: Objectives: To assess longitudinally small airway function in children born extremely prematurely and whether there was a correlation between airway function in infancy and at 11‐14 years. Working Hypotheses: There would be tracking of airways obstruction ands mall airway function would deteriorate during childhood in those born extremely prematurely. Study Design: A longitudinal study. Patient‐Subject Selection: Thirty‐five children with a mean gestational age of 26 weeks had lung function assessed at 1 year corrected and 11‐14 years of age. Methodology: Lung volumes were measured by helium gas dilution (FRCHe ) and plethysmography (FRCpleth ) and small airway function assessed by calculating the FRCHe :FRCpleth ratio. Airway function was assessed at 1 year corrected by measurement of airway resistance (Raw ) and at 11‐14 years by assessment of Raw, forced expiratory flow from 75% of vital capacity (FEF75 ), and forced expiratory volume at one second (FEV1 ). Results: At the first assessment, the children had a mean (SD) FRCHe :FRCpleth of 0.90 (0.13) and at the second, 0.83 (0.12) ( P = 0.035). There was a significant 0.54% decrease (95%CI: −1.02%, −0.06%) in FRCHe :FRCpleth for increased age per year after adjusting for birth weight, gestational age, sex, and bronchopulmonary dysplasia ( P = 0.027). There were significant correlations between Raw at the first assessment and Raw ( P = 0.012), FEF75 ( P = 0.034), and FEV1 ( P = 0.04) at 11‐14 years. Conclusions: These results demonstrate in those born extremely prematurely there is tracking of airway function during childhood.